Management of Urban Parking Lot Energy Efficiency with the Application of Wind Turbine and LED lights - Bekir Z Yuksek; Ulan Dakeev (Bulletin of Electrical Engineering and Informatics, 2014)
A study of a parking lot lighting of a large manufacturing company in Iowa was implemented to evaluate monthly energy consumption. Mercury light bulbs with 227W ratings on the light poles were replaced with low power energy efficient LEDs to increase the overall efficiency. Additionally, a small scale wind turbine was installed to supply power to experimental light poles. Migration from the current gas bulbs to the LED light results yielded about 60% energy savings, while capital gains due to the generation of wind energy returned about 80% savings per month which recovered initial investments on the assets. The environmental impact of this study cannot be neglected and it also provided opportunity for STEM education in colleges and wind energy awareness in the society in Iowa by showing benefits from current experiments. Details of the methods and analyses should be particularly useful to urban planners because they show how standard references on investment in automobile parking should be modified to include efficient energy management. The authors proposed new way to limit the cost of energy consumptions and environmental pollution on wildlife and human health. Research implications are discussed in terms of the impact of natural features in urban areas for reduction of green house gas emissions and promoting alternative energy sources.